Analysis of Tourist Arrival in Nepal - Sharma, Laxmi Kanta; Ghimire, Ambika (Cognition, 2019)
The present paper is prepared based on review of literature and secondary data with an objective to analyze the trend of tourist arrivals in Nepal in last eighteen years. Attempt has been made to capture different aspects of tourist arrivals in Nepal. Rate of tourist arrival in Nepal has been found increasing since 2016 with decreasing rate of average expenditure per visitor. Nepal has been formally open for international tourists since 1951 and mountain tourism is the pioneer of all. The overall average length of stay of tourists in Nepal is about 11.77 days for last 18 years. Nepal is popular destination for youths and adults. The fraction of tourist arrival from five countries are; India (16.57%), China (13.1%), USA (7.83%), Sri lanka (5.94%) and United Kingdom (5.41%). The percentage of male tourist visiting Nepal has been found ever larger than female and major purpose of tourists travelling to Nepal is for the Holiday Pleasure.